World rabbit production - Szendrő, Zsolt; Szendrő, Éva (Acta Agraria Kaposváriensis, 2007)
The world’s largest rabbit meat producer (460.000 tons in 2004) and exporter (6.397 tons) is China but their import is negligible. Italy is Europeans’s leading producer (second of the world: 222.000 tons). Italy’s rabbit meat import was the largest worldwide between 1990 and 1994 but in 2004 it was at the 4th position (2.320 tons). With its decreasing import the export is increasing and it reached 6.231 tons in 2003. Spain is at the second position in the European production (100.610 tons in 2004). With the increasing production it is among the top five countries in export (4.629 tons in 2004) but its import is small (441 tons in 2004). The largest importer country is Germany (7.589; 4.958 and 4.487 tons in 2002, 2003 and 2004, respectively). Its production was between 33.000 and 34.000 tons (between 1990 and 2004) but the export was small. The Netherlands is among the five countries that are exporting the largest amount of rabbit meat. They owned the first position (8.940 tons in 1998; 11.187 tons in 2001) then the second position (3.574 tons in 2004) after China. Hungary is at the 10th position in rabbit production (7.500 tons in 2004) and the country is among the leading exporters having the second-third place of the world (5.391 tons in 2004) but the country has no import at all.